Talent retention as a strategic factor of organisational sustainability - Bolshakova, Alevtyna (Запоріжжя: ТДАТУ, 2026)
Retaining talented employees is crucial for organizational success and innovation. Once seen as an HR concern, talent retention is now a strategic goal vital for competitiveness and long-term survival. With rising competition for skilled staff, organizations must prioritize keeping top talent to ensure operational effectiveness, continuity, and growth.
Keywords: talent retention; organisational sustainability